PENINGKATAN STRATEGI PEMASARAN DAN BRANDING UMKM DESA PENTUR KABUPATEN BOYOLALI MELALUI DIGITAL MARKETING - Andriani Kusumaningrum; Sri Harjanto; Sri Siswanti; Setiyowati Setiyowati; Mita Purwati; Retno Tri Vulandari (Sekolah Tinggi Ilmu Ekonomi AMA, 2023)
Economically, most of the residents of Pentur Village are farmers, both working in paddy fields and fields, apart from that, it is also a center for the bamboo woven craft industry which is the livelihood of some of the residents. In fact, Pentur village also has a fairly well-known foundation called